On the multifarious activities of the educator Shakir Mukhtarov in Turkestan - Alisher A. Isokboev (Историческая этнология, 2025)
The article describes the famous Tatar educator Shakir Mukhtarov’s work in organizing new-method schools in Turkestan. His speeches in the Muslim press of Turkestan and Central Russia, participation in the development of the national press and printing houses have been analyzed. Special attention is drawn to the role of Shakir Mukhtarov in progressive political processes in the Turkestan region. It has been concluded that the Tatar scholar Shakir Mukhtаrov was one of the founders of new-method schools in Turkestan. He studied the work of new methodological schools, which had been opened in the region, and was engaged in the coverage of their activities in the newspapers of that time. Mukhtarov’s commitment to national education was recognized in the Turkish-Muslim press. Mukhtarov played a major role in the publication of the newspapers Tarakiy, Shukhrat, and Osiyo when he lived in Kokand. It turned out that the enlightened Tatars living in this city formed a political association, the Young Party, which contributed to the spread of the Jadidism movement. The article reveals the essence of Sh. Mukhtarov’s articles based on progressive ideas disseminated in the Shuro magazine, which was published in Orenburg. The work reveals the extensive educational activities of Sh. Mukhtarov in the Turkestan Jadidist movement.